2018
DOI: 10.1016/j.freeradbiomed.2018.04.548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humidity on photoinduced radicals in human hair

Abstract: EPR spectroscopy was used to monitor formation of free radicals in human hair upon UV irradiation. While the EPR spectra of brown hair were dominated by melanin signal, those of white hair were keratin-derived. The decay of UV induced keratin radicals was enhanced at increased ambient humidity. We argue that at higher humidity the swollen hair provides a more liquid-like environment, and higher molecular mobility in this environment leads to faster radical reactions. This interpretation is consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The paper by Groves et al looking at the effect of increased RH on the EPR spectrum of white hair supports this hypothesis. At maximum humidity (100% RH), the EPR peak due to sulphur radicals is much higher than in dry hair, which supports the idea that reaction of Tyr radicals with Cys increases in the presence of water because of increased molecular mobility and O 2 availability within the fibre.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The paper by Groves et al looking at the effect of increased RH on the EPR spectrum of white hair supports this hypothesis. At maximum humidity (100% RH), the EPR peak due to sulphur radicals is much higher than in dry hair, which supports the idea that reaction of Tyr radicals with Cys increases in the presence of water because of increased molecular mobility and O 2 availability within the fibre.…”
Section: Resultsmentioning
confidence: 88%
“…Previous work showed that NAC can react with Tyr phenoxy radicals , which are believed to be the free radicals responsible for the intrinsic EPR spectrum of wool and white hair . We subsequently ran an EPR spectrum of NAC‐treated white hair before UV exposure, which showed that the weak feature shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…46 EPR spectroscopy was also used in studies of melanin biopolymers from Substantia nigra, skin, eyes, and hair. [47][48][49][50] o-Semiquinone free radicals were identified by us earlier in normal human melanocytes, A-2058 tumor cells, and in melanin isolated from A-375 and G-361 human melanoma malignum cells. [11][12][13][14] The free radical concentrations in the all A-2058 cells cultured with SIM were lower than in the control cells.…”
mentioning
confidence: 92%